The effectiveness of ventilator weaning using a weaning protocol compared to non-protocol: a systematic review - Denissa Faradita Aryani; Rr. Tutik Sri Hariyati; Elly Nurachmah (Healthcare in Low-resource Settings, 2024)
Ventilator use can reduce respiratory function, heighten infection risk, extend ventilator dependence, and, in severe cases, necessitate prolonged mechanical ventilation. Systematic weaning protocols can alleviate these issues, enhance breathing, and aid extubation. This review assesses studies on weaning protocols in ICU patients. Using the PRISMA framework, an extensive search was performed in databases such as ClinicalKey Nursing, ScienceDirect, ProQuest, SAGE, EMBASE, MEDLINE, Scopus, SpringerLink, and PubMed. This search aimed to find studies comparing protocolized and non-protocolized weaning in adult ICU patients. Included were peer-reviewed randomized controlled trials (RCTs) and quantitative studies focusing specifically on adult ICU weaning protocols. Studies involving non-adult populations were excluded. The JBI and CASP tools were used to assess the quality of the studies. Out of 475 identified articles, six met the inclusion criteria. Three types of weaning protocols were identified: nurse-led, respiratory therapy-led, and automatic protocols. These protocols demonstrated effectiveness by reducing ventilator time, increasing extubation success, and shortening ICU stays. Evidence supports that weaning protocols positively impact patient outcomes, particularly by shortening intubation periods, and can enhance inter-professional collaboration in the ICU.